Motor neurone disease: Further evidence for an abnormality of nerve metabolism - Shahani, Bhagwan (1971)
Physiological and biochemical studies were carried out on 16 patients with motor neurone disease (MND). It was confirmed that the peripheral nerves in cases of MND are often unusually resistant to ischaemia especially as regards the large sensory fibres. Biochemical investigations demonstrated a tendency to carbohydrate intolerance and abnormal pyruvate metabolism. When compared with other related studies in MND it seems very likely that there is a metabolic abnormality present in MND which demands further study.